Software quality and certification: Perception and practices in Malaysia - Yahaya, Jamaiah; Deraman, Aziz; Hamdan, Abdul Razak (Universiti Utara Malaysia Press, 2006)
Recently, there has been an increasing amount of literature on software quality and at the same time complaints are reported widely on the quality status of software products. In the past few years, we have seen a tremendous growth of companies and agencies involved in the software industries not only in Malaysia but also in the entire world. The emergence of Multimedia Super Corridor (MSC) in Malaysia in 1996 was the starting point for the blooming of software and ICT related companies. Despite that, not much attention is given to the quality of software product that is being developed by various categories of companies. These companies could not justify the quality of their products to users and these users are left with uncertainties on the quality of software. This study was conducted to investigate the current practice and perception on software quality and assessment in Malaysian industries. A total of 43 organizations were surveyed to answer several issues on quality and certification. Some of the important findings from this survey were the need for standard and mechanism in software assessment, and the need for independent party certification to justify the quality status of software products. This paper discusses more findings of this survey.